A novel nonlinear sliding mode controller for a single stage grid-connected photovoltaic system. (December 2020) - D., Menaga; Sankaranarayanan, V.
Abstract: A nonlinear sliding mode controller is proposed for a single stage grid-connected photovoltaic system with a novel nonlinear sliding surface. The proposed controller is designed to ensure maximum power extraction with unity power factor. There are two main advantages of the proposed sliding surface. The new surface will results in a first order sliding mode controller. The second advantage is that maximum power extraction is achieved by tracking DC-link voltage ( V d c ) of the PV system. The proposed controller is also compared with the existing sliding mode controller in terms of both numerical simulation and experimental results. It is found that, the proposed controller's performance is better than the existing controller in terms of power extraction and more robust when there are uncertainties and disturbance in PV system.